Effects of a 5-week resistance training program on muscle strength, muscle power, and balance of older adults - Guinto, Jonas Victor 2001-
Numerous physical and cognitive changes can be inevitably brought about by aging. Muscle weakness, visual impairment, balance problems, and limited mobility are widespread among the geriatric population, especially in the Philippines. Unfortunately, these impairments led to the increased occurrence of falls in the Philippines. Falls are one of the leading causes of death in the country. To help solve this problem, certain interventions, such as resistance training and aerobic training, have been done by researchers to reduce and delay the occurrence of physical and cognitive impairments, consequently reducing the occurrence of falls. However, the literature regarding resistance training within the geriatric population in the country is still lacking. Given this, the study aimed to create a resistance training program suitable for the geriatric population and determine its effects on their muscle strength, power, and balance. Four (4) healthy older adults, aged 60 years old and above, were chosen and asked to participate in a 5-week training program devised by the researcher. Pre- and posttests were done to measure muscle strength, muscle power, and balance of participants. After the 5-week training period, the training program was analyzed in terms of its effects on the participants’ muscle strength, muscle power, and balance based on the pre-and post-test results. The study has found that the intervention was effective in improving the muscle strength, muscle power, and balance of the participants. Even though certain factors must still be considered, and further research must still be done, the devised training program can be used as an effective training modality in improving the muscle strength, muscle power, and balance of older adults.